2018
DOI: 10.1002/adsc.201701285
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Promoted Decarboxylative Giese Reactions of α‐Aryl Ethenylphosphonates and the Application in the Synthesis of Fosmidomycin Analogue

Abstract: An approach for the synthesis of α‐aryl alkylphosphonates based on visible‐light photocatalytic Giese reaction of α‐aryl vinylphosphonates with aliphatic carboxylic acids has been successfully developed. This protocol tolerates a wide range of functional groups and shows broad substrate scope with regard to both the carboxylic acid and vinylphosphonate components. With sequential Giese/hydrolysis reactions as the strategy, the oxo‐phosphonates could be easily accessible. The synthetic application of the hydrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…We found that 3ab ′ can be successfully converted into a corresponding product Fosmidomycin analogue 5ab ' in 92% yield. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…We found that 3ab ′ can be successfully converted into a corresponding product Fosmidomycin analogue 5ab ' in 92% yield. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported a new method for the preparation of 1‐aryl cyclopropylphosphonates via photoredox neutral‐catalyzed cyclopropanation of vinylphosphonates with chloromethyl silicate as the methylene source (Scheme c, path I) . Inspired by our interest in the application of radical‐polar crossover process based on radical addition to vinylphosphonates, we envisioned that the intermediate of γ‐halo‐α‐phosphoryl carbanion for the 3‐ exo ‐ tet cyclization could be accessible via alkyl radical addition to 1,1‐disubstituted alkenes and the following single‐electron reduction (Scheme c, path II) . Moreover, the photoredox‐catalyzed allylation/cyclopropanation cascade reaction would be realized via radical addition/fragmentation of allylic halides with halomethyl radical followed by radical addition‐polar cyclization between the excess halomethyl radical and homoallylic halide generated in situ (Scheme c, path III).…”
Section: Methodsmentioning
confidence: 99%
“… 141 Also, the Fukuzumi catalyst (9-mesitylene-10-methylacridinium perchlorate, [Acr + Mes]ClO 4 ) can promote this Giese-type reaction, 142 allowing the alkylation of α-aryl ethenylphosphonates for the synthesis of fosmidomycin analogues. 143 …”
Section: Formation Of a C(sp 3 )-C Bondmentioning
confidence: 99%